Transcutaneously refillable, 3D-printed biopolymeric encapsulation system for the transplantation of endocrine cells. (September 2018) - Farina, Marco; Chua, Corrine Ying Xuan; Ballerini, Andrea; Thekkedath, Usha; Alexander, Jenolyn F.; Rhudy, Jessica R.; Torchio, Gianluca; Fraga, Daniel; Pathak, Ravi R.; Villanueva, Mariana; Shin, Crystal S.; Niles, Jean A.; et al.
Abstract: Autologous cell transplantation holds enormous promise to restore organ and tissue functions in the treatment of various pathologies including endocrine, cardiovascular, and neurological diseases among others. Even though immune rejection is circumvented with autologous transplantation, clinical adoption remains limited due to poor cell retention and survival. Cell transplant success requires homing to vascularized environment, cell engraftment and importantly, maintenance of inherent cell function. To address this need, we developed a three dimensional (3D) printed cell encapsulation device created with polylactic acid (PLA), termed neovascularized implantable cell homing and encapsulation (NICHE). In this paper, we present the development and systematic evaluation of the NICHE in vitro, and the in vivo validation with encapsulated testosterone-secreting Leydig cells in Rag1−/− castrated mice. Enhanced subcutaneous vascularization of NICHE via platelet-rich plasma (PRP) hydrogel coating and filling was demonstrated in vivo via a chorioallantoic membrane (CAM) assay as well as in mice. After establishment of a pre-vascularized bed within the NICHE, transcutaneously transplanted Leydig cells, maintained viability and robust testosterone secretion for the duration of the study. Immunohistochemical analysis revealed extensive Leydig cell colonization in the NICHE. Furthermore, transplanted cells achieved physiologic testosterone levels in castrated mice. The promising results provide a proof of concept for the NICHE as a viable platform technology for autologous cell transplantation for the treatment of a variety of diseases.